2012
DOI: 10.3103/s0095452712010112
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of tyrosine kinases and phosphatases as a tool for the investigation of microtubule role in plant cold response

Abstract: Tyrosine phosphorylation plays a vital role in the variety of signal transduction pathways in eukaryotic cells, however its role and relevance in plants are still largely unknown. To investigate the functional role of tubulin tyrosine phosphorylation in plant cells the interplay between the effects of tyrosine kinases (herbimycin A) as well as tyrosine phosphatases (sodium orthovanadate) inhibitors on microtubules sensitivity to cold in A. thaliana root cells were studied. Since it was found that inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Moreover, the cytoskeleton is affected, directly or indirectly, by reversible Tyr phosphorylation (Luan , ; Tonks ). Tyr phosphorylation appears to be important for the stability and organization of MTs in different types of plant cells (Yemets et al ; Sheremet et al ). It was demonstrated that both α‐ and β‐subunits of plant tubulin undergo phosphorylation on Tyr residues (Blume et al ; Nemoto et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the cytoskeleton is affected, directly or indirectly, by reversible Tyr phosphorylation (Luan , ; Tonks ). Tyr phosphorylation appears to be important for the stability and organization of MTs in different types of plant cells (Yemets et al ; Sheremet et al ). It was demonstrated that both α‐ and β‐subunits of plant tubulin undergo phosphorylation on Tyr residues (Blume et al ; Nemoto et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Tyr phosphorylation has an important role in plant signalling (Ghelis et al 2008;Nemoto et al 2015). Moreover, it has been reported that the cytoskeleton is affected, directly or indirectly, by reversible Tyr protein phosphorylation (Luan 2002(Luan , 2003Tonks 2006;Blume et al 2008;Yemets et al 2008;Sheremet et al 2012;Fujita et al 2013). However, molecular mechanisms of Tyr phosphorylation and signalling pathways mediated by this modification in plants are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…29 In turn, cortical MTs in epidermal cells of the transition zone are exceptionally responsive to fluctuations of auxins 30 and nitric oxide content, 4 protein kinase/phosphatase inhibitors 31 and cold treatment as well. 32 We have shown also that immediately after the UV-B exposure (13.6-68 kJ/m 2 ) cortical MTs in both transition and elongation zones depolymerized rapidly. 26 Furthermore, UV-B-induced MTs reorganization in root cells of shielded A. thaliana seedlings was accompanied by primary root growth inhibition (Fig.…”
Section: Acknowledgmentsmentioning
confidence: 56%
“…Thus, MTs of cold acclimated spinach mesophyll cells coped better with the consequences of a freeze-thaw cycle [9,66]. MT stabilization under the influence of low tempera tures can be also provided by phosphorylation of α or β tubulins on serine, threonine, and tyrosine residues [67]. In addition, in various winter wheat cultivars, the high content of phosphorylated 60 kD proteins, may be comprising actin and tubulin, was accompanied by a decrease in MT cold resistance [65].…”
Section: Aba and Microtubulesmentioning
confidence: 97%